If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3 = 95 Reorder the terms: -3 + 2x = 95 Solving -3 + 2x = 95 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2x = 95 + 3 Combine like terms: -3 + 3 = 0 0 + 2x = 95 + 3 2x = 95 + 3 Combine like terms: 95 + 3 = 98 2x = 98 Divide each side by '2'. x = 49 Simplifying x = 49
| 35=-8(7n+9) | | 2/3*4-7= | | 87567+876768x=8768-786878x | | 8x+2+2x=3+4 | | 7y+18=81 | | 3x-43=2x+13 | | -2x+10=5x-11 | | 2/3*8-7= | | 6x+12=-4x+12 | | 11y+4=15 | | 210=58-x | | -7n+3n=-3 | | 7x+2=-5+5x+13 | | -9x^3=-x^5 | | 2+8v=-22 | | -2y-7=3y+23 | | 111=-3(4x-5) | | 2(-1)+8y=-32 | | 3x-2=8-4x | | 2(4x-3x)-8=4+2x | | 6x^2+10=17x | | -5b=-50 | | 10x+22-5=8(4x+7) | | 97-u=265 | | 27x-27y=81 | | 8A-40=4A+60 | | -8w-14=-9 | | 7(6-2a)=5(-3a+2) | | 2y-5=3(3-r) | | 16x-16=16(4x-1) | | 4b-6-(b+2)= | | -60-7=67 |